The effect of family counseling on performance scales of quality of life ofwomen with breast cancer undergoing chemotherapy - Samiei siboni1, fatmhe; Anoosheh, monireh; Alhani, fatmeh; Haji Zadeh4, ebrahim (Advances in Nursing & Midwifery, 2011)
Abstract Background and aim In women with cancer, the quality of life and their performance level would be affected, thus awareness about patient quality of life helps the nurses to lead their care for improving the patients’ quality of life. Despite of majority of performed studies, the emphasis is on patients’ problems rather than families, So it is necessary for improving the patient quality of life to take into consideration those factors which are important for family .The purpose of this study was to determine the effect of consultation with family on performance scale of women’s quality of life with breast cancer undergoing chemotherapy. Materials and methods This research is a semi-experimental study,70 married women aged 30-55 years old who had at least 1child older than 15 year , undergoing chemotherapy with previous record of mastectomy and they have been referred to clinics located in two cities, Qazvin and Zanjan, were included in the study. Participants were allocated in two -experiment and control-groups. For subjects in experiment group 8 consultation sessions with family was designed, the sessions were held with the presence of patient, spouse and children .The patients’ quality of life in both groups was measured at the beginning and at the end of final consultation session. Quality of life was assessed by the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) and its supplementary breast cancer measure (QLQ-BR23) .The data were analyzed using SPSS version 15. Findings Results showed that quality of life of patients who had participated in consultation sessions was improved (P<0/05).The improvement was seen in physical functioning, emotional, role functioning ,cognitive and social functioning subscales of quality of life measure, andin body image, sexual functioning , sexual enjoyment and future perspective subscales of BR 23 questionnaire. Conclusion with respect to present research’s findings which demonstrate the effect of consultation with family on improvement of patients’ performance level, hence the family can have a particular position on protecting patients and improvement quality of life, therefore it is offered the designed program of taking consult with family would be applied as an affective way on improvement quality of life for these patients. Keywords: Breast Cancer, Chemotherapy, quality of life, family counseling